PENENTUAN ONSET MONSUN DI WILAYAH INDO-AUSTRALIA BERDASARKAN LOMPATAN ITCZ - Didi Satiadi; Ibnu Fathrio (Jurnal Sains Dirgantara, 2011)
Inter-Tropical Convergence Zone (ITCZ) is one of the factors affecting weather and climate in the Indonesia Maritime-Continent Region together with El-Niño Southern Oscillation (ENSO), Indian Ocean Dipole Mode (IODM), Madden Julian Oscillation (MJO), Tropical Cyclone (TC), and Monsoon. ITCZ influence weather and climate in the Indonesia region. Therefore, monitoring and understanding ITCZ behaviour become important as an alternative method to predict variability, anomaly, and extreme atmospheric conditions in Indonesia region. Research has been conducted to study the behaviour of ITCZ in the Indonesia maritime-continent region using Multi-Functional Transport Satellite (MTSAT) data from year 2006 to 2009. Identification of ITCZ and its movement was carried out based on minimum cloud top temperature observed by MTSAT satellite. Meridional movement of ITCZ were then compared to the Indo-Australia Monsoon Indices and rainfall from Tropical Rainfall Measuring Mission (TRMM) satellite. The results showed that ITCZ positions tend to exist at certain locations and experienced jumps to mid-latitude during seasonal change to dry and wet seasons. The results can be used to predict monsoon onset in the Indo-Australia region based on ITCZ jumps, and also to verify rainfall prediction models which in turn can be applied to hydrological models, environtmental models, and rainfall-related disaster early warning systems. Keywords: ITCZ, Monsoon, Onset, Satellite, Indonesia